2017
DOI: 10.1111/bju.13924
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐vascular endothelial growth factor treatment decreases bladder pain in cyclophosphamide cystitis: a Multidisciplinary Approach to the Study of Chronic Pelvic Pain (MAPP) Research Network animal model study

Abstract: Objective To investigate whether treatment with anti-VEGF (vascular endothelial growth factor) neutralizing antibodies can reduce pain and voiding dysfunction in the cyclophosphamide (CYP) cystitis model of bladder pain in mice. Materials and Methods Adult female mice received anti-VEGF neutralizing antibodies (10 mg/kg intraperitoneal B20-4.1.1 VEGF mAb) or saline (control) pre-treatment, followed by CYP (150 mg/kg intraperitoneal) to induce acute cystitis. Pelvic nociceptive responses were assessed by appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 27 publications
1
20
0
1
Order By: Relevance
“…The basic research findings have shown that intravesical instillation of VEGF modulated sensory and motor nerve plasticity, and, consequently, bladder function and visceral sensitivity in rats . In addition, systemic anti‐VEGF neutralizing antibody pretreatment significantly reduced the pelvic nociceptive response to cyclophosphamide‐induced cystitis compared with controls in rats . Furthermore, it has recently been reported that VEGF was thought to be one of the crucial urine markers to discriminate IC/BPS patients from OAB patients, and that urinary symptom and pain severity was significantly correlated with urinary VEGF levels in female IC/BPS patients .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The basic research findings have shown that intravesical instillation of VEGF modulated sensory and motor nerve plasticity, and, consequently, bladder function and visceral sensitivity in rats . In addition, systemic anti‐VEGF neutralizing antibody pretreatment significantly reduced the pelvic nociceptive response to cyclophosphamide‐induced cystitis compared with controls in rats . Furthermore, it has recently been reported that VEGF was thought to be one of the crucial urine markers to discriminate IC/BPS patients from OAB patients, and that urinary symptom and pain severity was significantly correlated with urinary VEGF levels in female IC/BPS patients .…”
Section: Discussionmentioning
confidence: 99%
“…14 In addition, systemic anti-VEGF neutralizing antibody pretreatment significantly reduced the pelvic nociceptive response to cyclophosphamide-induced cystitis compared with controls in rats. 15 Furthermore, it has recently been reported that VEGF was thought to be one of the crucial urine markers to discriminate IC/BPS patients from OAB patients, 8 and that urinary symptom and pain severity was significantly correlated with urinary VEGF levels in female IC/BPS patients. 16 Taken together, these findings suggest that the increased VEGF levels in bladder tissues or urine, which could be correlated with angiogenesis, may provide new insights into the pathophysiological basis of IC/BPS.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-VEGF drugs are also used to attenuate neovascularisation in age-related macular degeneration and diabetic macular oedema (Ferrara, 2004 ; Kim and D'Amore, 2012 ). However, in recent years, the role of the VEGF family in neuroprotection and nociception has received increased attention (Beazley-Long et al, 2013 , 2018 ; Hulse et al, 2014 , 2015 , 2016 ; Selvaraj et al, 2015 ; Hulse, 2017 ; Lai et al, 2017 ). The involvement of VEGF in the pathophysiology of pain is not fully understood, however, the association between this growth factor and some of the main hallmarks of painful diseases warrants the investigation of VEGF as a therapeutic target for pain treatment.…”
mentioning
confidence: 99%
“…Notably absent from these increased analytes were cytokines such as IFNg, IL12b (P40 and P70), implicated in another model of CP/CPPS 30 , and IL17. VEGF expression was also shown to be increased in the NPI prophylactic group compared to either CP1 alone or NPI alone, which is interesting given that studies have shown that blockade of VEGF by an antibody reduced pelvic nociceptive responses in cyclophosphamide (CYP) cystitis 31 .…”
Section: Discussionmentioning
confidence: 83%